Analyzing the recency effects on long series audit information and its mitigation methods with group discussions - Yolanda Christina Rambing; Intiyas Utami; Ika Kristianti (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study aims to examine the recency effect that occurs due to the effect of sequences on long series audit information and test the effectiveness of group discussion to improve the decision quality. The recency effect is a tendency to give more weight to the latest information compared to other information received. Therefore, it is necessary to provide a method for mitigating the recency effect by using group discussion. This study used a 2x2x2 experimental design for a subject with 81 participants from accounting students. The results show that the individual decision quality that experienced the recency effect due to positive-negative and negative-positive sequential information after group discussion became better than before group discussion. The individual decision quality that experienced the recency effect due to positive-negative simultaneous information could not be mitigated by group discussion. Group discussion is an effective method for overcoming the recency effect on sequential information rather than on simultaneous information. Therefore, group discussion can be used as a strategy to reduce recency effects and improve the quality of audience decisions.